Haematology and plasma chemistry of breeding olive ridley sea turtles (Lepidochelys olivacea) - Meneses Guevara, Ana (2007)
THE olive ridley turtle (Lepidochelys olivacea) is the smallest species of living sea turtle. It is primarily carnivorous and highly migratory, with a pantropical distribution in the Atlantic, Pacific and Indian oceans (Plotkin 2003). The species is classified as globally endangered (IUCN 2002). Since the 1990s, there has been increasing interest in the health status of free-ranging sea turtles, but data are lacking for the olive ridley turtle. To the authors’ knowledge, only fragmentary data are available on the haematology (Thorson 1968, Frair 1977) and biochemistry (Dessauer 1970) of this species. These data are important in the clinical evaluation of the health of free-ranging animals, the results of which could be used to evaluate the health status of captive animals.